REDUCING PAEDIATRIC ANXIETY PRE- OPERATIVELY: STRATEGIES FOR NURSES - St. Onge, Angela (Operating Room Nurses Association of Canada Journal, 2012)
The surgical process can anxiety in children and this anxiety can be associated with both short and long term negative outcomes.4,5 Reduced pre-operative anxiety can improve both the child’s and family’s surgical experience. This article identifies strategies for nurses to address this issue, including: a child-focused approach, distraction techniques, and informed parental presence.